Are You an E-consumer? A Case Study on Finding Factors Impacting Consumers' Purchase Behaviour and Their Willingness to Pay on Average on E-Commerce Platforms in Malaysia - Nur Syafiqah Binti Mohamed Saleh; Nur Syifa` Binti Rosli; Nur Syafiqah Binti Halimi; Nur Syaida Ilyana Binti Badrul Hisham; Ankita Lahanu Gangurde (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
Online shopping has become phenomenal in this modern day. Moreover, the world was hit by the enormous Covid-19 pandemic. In the third quarter of 2021, e-commerce platform growth soared up to 17.1% and elevated our country’s GDP. People have become more comfortable buying things through the e-commerce platform than physically buying. These platforms unintentionally affect e-consumer behaviour. This research aims to study consumer behaviour on how much money a person spends on average on e-commerce platforms, mainly for online shopping. A total of 150 consumers were surveyed via Google form. The findings show that consumer purchase behaviour is directly related to price, customer satisfaction with their buying experience and information quality. Consumers are not affected by the convenience variable as profoundly as by other variables tested in this study. The collected data may be inaccurate because the investigation is tested on a survey.